Cultural Evolution Branches Out: The Phylogenetic Approach in Cross-Cultural Research. (May 2013) - Currie, Thomas E.
Recently there has been a movement in the social sciences to apply theories and methods developed originally in evolutionary biology to understand human behavior and cultural change. In this article, I highlight an ever growing branch of this research that analyzes cultural data using a suite of techniques based on evolutionary trees. These phylogenetic methods fall into two categories: (a) "tree-building" that is, inferring the historical relationships between units, and (b) comparative analyses that is, mapping other traits onto the tips of these trees to make inferences about trait evolution. Using lexical data I infer the phylogenetic relationships between 82 Indo-European languages. The estimated divergence time of these languages agrees with earlier studies in supporting a hypothesis that places the homeland of the Indo-Europeans somewhere in Anatolia 8000-9500 BP. Using data from Austronesian-speaking societies I give examples of the use of comparative methods to (i) infer the system of land tenure in ancestral societies, (ii) examine the ecological correlates of violence in the Polynesian and Micronesian societies, and (iii) test hypotheses about the mode and tempo of sociopolitical evolution. I examine future areas of cultural phylogenetic research in the evolutionary social sciences and argue that the kinds of studies introduced in this article hold the potential for fruitful collaborations between cultural phylogeneticists and cross-cultural researchers.